Problematization educational intervention to promote healthy habits in elderly people with diabetes: randomized clinical trial - Borba,Anna Karla de Oliveira Tito (2020)
ABSTRACT Objective: to assess the effects of a problematization educational intervention to promote healthy habits in elderly people with diabetes. Methods: a randomized clinical trial conducted with 202 individuals drawn for the intervention group and the control group. The intervention consisted of problematization educational activities on a monthly basis for over six months. The control group participated in conventional monitoring at the health unit. Data were collected through semi-structured interviews before and after the intervention, in addition to laboratory tests. Results: after the intervention, when compared to the control group, there was an increase in knowledge about the disease (p<0.001), positive attitude towards self-care (p=0.011), physical activity (p=0.020), diet variety (p=0.002), and lower consumption of oils and fats (p<0.05). Conclusion: the intervention performed has a beneficial effect to promote healthy habits.